Views on evolvability of embedded systems - Laar, Piërre van de; Punter, Teade; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Evolvability, the ability to respond effectively to change, represents a major challenge to today's high-end embedded systems, such as those developed in the medical domain by Philips Healthcare. These systems are typically developed by multi-disciplinary teams, located around the world, and are in constant need of upgrading to provide new advanced features, to deal with obsolescence, and to exploit emerging enabling technologies. Despite the importance of evolvability for these types of systems, the field has received scant attention from the scientific and engineering communities. Views on Evolvability of Embedded Systems focuses on the topic of evolvability of embedded systems from an applied scientific perspective. In particular, the book describes results from the Darwin project that researched evolvability in the context of Magnetic Resonance Imaging (MRI) systems. This project applied the Industry-as-Laboratory paradigm, in which industry and academia join forces to ensure continuous knowledge and technology transfer during the project's lifetime. The Darwin project was a collaboration between the Embedded Systems Institute, the MRI business unit of Philips Healthcare, Philips Research, and five Dutch universities. Evolvability was addressed from a system engineering perspective by a number of researchers from different disciplines such as software-, electrical- and mechanical engineering, with a clear focus on economic decision making. The research focused on four areas: data mining, reference architectures, mechanisms and patterns for evolvability, in particular visualization & modelling, and economic decision making. Views on Evolvability of Embedded Systems is targeted at both researchers and practitioners; they will not only find a state-of-the-art overview on evolvability research, but also guidelines to make systems more evolvable and new industrially-validated techniques to improve the evolvability of embedded systems.
Views on Evolvability of Embedded Systems; Foreword; Preface; Acknowledgements; Contents; Chapter 1 Researching Evolvability; Chapter 2 Architecting for Improved Evolvability; Chapter 3 Complementing Software Documentation; Chapter 4 Identifying and Investigating Evolution Type Decomposition Weaknesses; Chapter 5 Transferring Evolutionary Couplings to Industry; Chapter 6 An Execution Viewpoint Catalog for Software-Intensive and Embedded Systems; Chapter 7 Researching Reference Architectures Gerrit Muller; Chapter 8 A3 Architecture Overviews; Chapter 9 Linking Requirements and Implementation; Chapter 10 Workflow Modelling of Intended System Use; Chapter 11 Supervisory Control Synthesis in the Medical Domain; Chapter 12 Creating High-Quality Behavioral Designs for Software-Intensive Systems; Chapter 13 Verifying Runtime Reconfiguration Requirements on UML Models; Chapter 14 Scheduling in MRI Scans processing; Chapter 15 Strategy-Focused Architecture Decision Making; Chapter 16 Balancing Time-to-Market and Quality in Evolving Embedded Systems; Chapter 17 Industrial Impact and Lessons Learned; Chapter 18 Conclusions; Annex; I Darwin Publications; II List of Darwin Partners; Index
Electronic reproduction
Keywords: Adaptive computing systems; Embedded computer systems; Magnetic resonance imaging